Local patterns of diversity in California northern coastal scrub. Issue 15 (27th June 2018) - Wrubel, Eric; Parker, V. Thomas
Abstract: Within global biodiversity hotspots such as the California Floristic Province, local patterns of diversity must be better understood to prioritize conservation for the greatest number of species. This study investigates patterns of vascular plant diversity in relation to coast–inland environmental gradients in the shrublands of Central California known as northern coastal scrub. We sampled coastal shrublands of the San Francisco Bay Area at coastal and inland locations, modeled fine‐scale climatic variables, and developed an index for local exposure to maritime salts. We compared diversity, composition, and structure of the coastal and inland plots using indirect gradient analysis and estimated species accumulation using rarefaction curves. Coastal plots were significantly higher in alpha, beta, and gamma diversity than inland plots. Plant diversity (effective species number) in coastal plots was 2.1 times greater than inland plots, and beta diversity was 1.9 times greater. Estimated richness by rarefaction was 2.05 times greater in coastal sites than inland sites. Salt deposition and water availability were the abiotic process most strongly correlated with increased maritime plant diversity and compositional differences. Stands of northern coastal scrub on the immediate coast with higher maritime influence exhibit markedly higher plant diversity than most interior stands, paralleling previous work in other vegetation types in this region. These studies suggest that the California coastline deserves special consideration for botanical conservation. Fine‐scale climatic models of cloud frequency, water availability, and the salt deposition index presented here can be used to define priority areas for plant conservation in California and other coastal regions worldwide. Abstract : This research investigates local plant diversity in relation to environmental gradients in the shrublands of Central California. We present fine‐scale environmental models that can be used to identify local diversity hotspots.